Physicochemical and Heavy Metal Analysis in Industrial Wastewater: Impact on Biodiversity in Morang District, Koshi Province, Nepal - Shah, Sujit Kumar; Sah, Pankaj Kumar; Bhattarai, Ajaya (Butwal Campus Journal, 2024)
This study investigates the concentration of heavy metal ions in wastewater samples collected from various industrial facilities located in the Biratnagar-Rangeli corridor of Morang district. The physical and chemical parameters, such as pH, electrical conductivity (EC), biological oxygen demand (BOD), and chemical oxygen demand (COD) were measured, and the presence of heavy metals, including iron (Fe), Zinc (Zn), Chromium (Cr), Nickel (Ni), Lead (Pb), and Arsenic (As), was assessed. Atomic Absorption Spectrophotometer (AAS) (Thermo Scientific, ice3000 series, Thermo Fischer, USA) was used to measure heavy metals. The findings reveal elevated levels of these pollutants, particularly Iron (Fe) and Zinc (Zn), which exceed acceptable safety limits. The study also identifies potential impacts on biodiversity, human health, and the local ecosystem, with significant risks associated with long-term exposure.